Antioxidant and cytotoxic potentials of Streptomyces gilvigriseus MUSC 26T isolated from mangrove soil in Malaysia - Hooi-Leng Ser; Wai-Fong Yin; Kok-Gan Chan; Tahir Mehmood Khan; Bey-Hing Goh; Learn-Han Lee (Progress in Microbes and Molecular Biology)
Microorganisms play an important role in natural product discovery, particularly the member of genus Streptomyces. The Gram-positive, filamentous streptomycete, Streptomyces gilvigriseus MUSC 26T was firstly isolated from mangrove forest at Tanjung Lumpur, Malaysia. After 7-day fermentation, the supernatant of MUSC 26T was collected and subjected to chemical extraction. The resulting extract was used in antioxidant and invitro cytotoxicity assays against human colon cancer cell lines. The results showed that MUSC 26T extract possessed significant antioxidant activity and cytotoxic effect against the tested colon cancer cell lines. Lowest cell viability was observed in HCT-116 cell lines, at 63.64 ± 3.62 % (after treated with 400 μg/mL of extract). The other cell lines exhibited cell viability ranged from 67.50 – 86.66 % when treated with 400 μg/mL of extract. Further chemical analysis on the extraction using GC-MS has revealed the production of 14 compounds, including two cyclic dipeptides which could possibly contribute to the observed bioactivities. By the same token, the availability of its genome sequence allows further investigation into the biosynthetic gene clusters responsible for the production of these compounds which could essentially accelerate its development as chemopreventive drug(s).